Infant and child health and healthcare before and after COVID-19 pandemic: will it be the same ever? - Mortada El-Shabrawi; Fetouh Hassanin (SpringerOpen, 2020)
Abstract Background The novel corona virus disease 2019 (COVID-19) current pandemic is an unpreceded global health crisis. Not only infection of infants, children, and adolescents is a concern for their families and pediatricians, but there are also other serious challenges that should be properly identified and managed as well. Main body We have to identify and assess the different factors that have either direct or indirect effects on child health and healthcare due to COVID-19 pandemic and focus on the serious effects. It is easily realized that there are many challenging problems associated with COVID-19 with short-term effects that already appeared and need urgent solutions and long-term effects that are not yet well apparent and have to be searched for and properly addressed. Conclusions COVID-19 crisis has lots of impacts on child health and child healthcare, not only from the medical aspect but also from the social, psychological, economic, and educational facets. All these adverse implications have to be identified and dealt with on individual bases approach in the short and long term.